EPIDEMIOLOGICAL AND CLINICAL PROFILE OF HOSPITALIZATIONS IN THE MEDICAL CLINIC WARD OF THE CEILÂNDIA REGIONAL HOSPITAL - Oliveira Macedo, Allan; Borges da Silva Oliveira, Amarildo; Brauna Leite, Carina; Augusta Matos de Oliveira, Carolina; Siqueira Santos, Gheisa; Danicki Prado Fernandes, Jéssica; da Costa Ferreira, Luciana; Neves Frota Souza, Nábilla; Mitsue de Castro Matsuoka, Sarah; do Amaral Miranda, Thiago (Health and Society, 2024)
The objective of this work is to describe the quantitative and descriptive form of the profile of patients who were admitted to the Internal Medicine Infirmary unit of the Regional Hospital of Ceilândia in the Federal District between 01/07/2021 e 31/12/2021. The retrospective study will be carried out from the analysis of records. For a statistical analysis, the Excel® 2019 program will be used. Patients will export epidemiological data on sex, age, marital status, hometown, city of domicile, previous chronic illness, cause, and duration of immediate outcomes. It should be noted that the financial information acquired in the study can contribute to assistance and permanent education in the planning of the service.